‘My workspace, not yours’: The impact of psychological ownership and territoriality in organizations - Brown, Graham; Zhu, H. (Academic Press, 2016)
© 2016 Elsevier Ltd Despite the inherent need to own and widespread prevalence of owning and claiming in organizations, very little is known about the impact of psychological ownership and territoriality. Using a field survey across several organizations, we find that feelings of ownership and territorial behavior are directly related to positive feelings towards the object and that these feelings may also extend beyond the target object to feelings of commitment to the organization. On the downside, however, the impact of these claims also may affect coworker's perceptions of the territorial individual. The findings are consistent with past theorizing suggesting that territorial behavior may have positive psychological consequences but this same behavior may not be understood or may be viewed negatively by others. Specifically, we find that territorial behavior is negatively related to an individual's perceived power and performance. Thus, the benefits for the individual may be offset by other's negative perceptions of the people who are territorial. Implications of these findings and future research directions are discussed.